Effect of colon cancer and surgical resection on skeletal muscle mitochondrial enzyme activity in colon cancer patients: a pilot study. Issue 1 (31st May 2012) - Phillips, Bethan E.; Smith, Kenneth; Liptrot, Sarah; Atherton, Philip J.; Varadhan, Krishna; Rennie, Michael J.; Larvin, Mike; Lund, Jonathan N.; Williams, John P.
Abstract : Background: Colon cancer (CC) patients commonly suffer declines in muscle mass and aerobic function. We hypothesised that CC would be associated with reduced muscle mass and mitochondrial enzyme activity and that curative resection would exacerbate these changes. Methods: We followed age‐matched healthy controls and CC patients without distant metastasis on radiological imaging before and 6 weeks after hemi‐colectomy surgery. Body composition was analysed using dual energy X‐ray absorptiometry. Mitochondrial enzyme activity and protein concentrations were analysed in vastus lateralis muscle biopsies. Results: In pre‐surgery, there were no differences in lean mass between CC patients and age‐matched controls (46.1 + 32.5 vs. 46.1 + 37.3 kg). Post‐resection lean mass was reduced in CC patients (43.8 + 30.3 kg, P < 0.01). When comparing markers of mitochondrial function, the following were observed: pyruvate dehydrogenase (PDH) activity was lower in CC patients pre‐surgery ( P < 0.001) but normalized post‐resection and cytochrome c oxidase and pyruvate dehydrogenase E2 subunit protein expression were lower in CC patients pre‐surgery and not restored to control values post‐resection ( P < 0.001). Nuclear factor kappa‐B, an inflammatory marker, was higher in CC patients pre‐surgery compared to controls ( P < 0.01), returning to control levels post‐resection. Conclusion: Muscle mass was affected by surgery rather than cancer per se. PDH activity was however lower in cancer patients, suggesting that muscle mass and mitochondrial enzyme activity are not inextricably linked. This reduction in mitochondrial enzyme activity may well contribute to the significant risks of major surgery to which CC patients are exposed.